Characteristics of digital device users of adolescents and their degree of awareness - Al-Shammari, Abeer Jamil (Journal of Educational and Psychological Sciences, 2019)
The aim of this article is to know some characteristics of adolescents using digital devices and their awareness of them using، by using descriptive method and questionnaire on a purposive sample consisting of 699 from middle school students. The results showed that 70.8% of the students age 14-15 are the most popular users of digital devices and 52.4% use their personal devices three or more hours per day، and that 55.22% of the second of middle school students are the average most used for digital devices and 72.5% of students use the smart phone and 60.5% of students their parents are separate. In terms of the sample’s awareness of the use of these devices، the results showed that the highest awareness of the use of digital devices is the students of third year of middle school with an (M 85.76 & SD 17.96) especially I-PAD Tablet. The highest ages 14-15 were aware of digital devices with an (M 86.66 & SD 19.71) using their personal devices for an hour only a day. The parents who refer to "parents living in the same house" were the highest with an (M87.68 & 19.57) The results also showed that females students more aware of the use of digital devices with an (89.43 SD 18.89) and this article concluded to some recommendations.